1974
DOI: 10.1364/ao.13.001519
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of Color-Measurement Instrumentation

Abstract: In a statistical study of the variability of instrumental color-measurement data, two instruments (a Kollmorgen KCS-40 colorimeter-abridged spectrophotometer and a General Electric Recording Spectrophotometer equipped with a Davidson and Hemmendinger digital tristimulus integrator) provided three modes of measurement. Ten samples were measured 48 times in each mode. Frequency distributions were constructed for several colorimetric quantities, including tristimulus values, chromaticity coordinates, and color di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…For this reason the GMSI Index (25) was not used. Again sustaining that a colorimetric reading gives a more accurate measure (23,26).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…For this reason the GMSI Index (25) was not used. Again sustaining that a colorimetric reading gives a more accurate measure (23,26).…”
Section: Discussionmentioning
confidence: 95%
“…To assess staining, colorimetric measurements are performed with the spectrophotometer and not the gingival modification of the stain index (GMSI; 25). In this method the tooth is divided in four zones and colour intensity in each zone is scored by the criteria described by Lobene (0, no stain; 1, light stain; 2, moderate stain and 3, heavy stain; 23, 25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors have evaluated human color perception correlated to instrumental measurement. Marcus and Billmeyer 28 showed a correlation between ΔE*ab values and visual assessment over a limited region. Kuehni and Marcus 29 found that 50% of subjects could detect a color difference between specimens with a ΔE*ab value of one.…”
mentioning
confidence: 93%